Synthesis of ZnS Nanorods Coated by MoS2/N-Doped Carbon Nanosheets with Enhanced Sodium Storage Properties. Issue 2 (10th February 2021) - Liu, Yuan; Cai, Shu; Shen, Kaier; Li, Qianqian; Xie, Yao; Zuo, You; Sun, Xiaohong
Abstract : In order to obtain an excellent ZnS-based anode material for sodium-ion batteries (SIBs), a designed hierarchical nanostructure formed by ZnS hollow nanorods and uniform nanosheets was synthesized via hydrothermal method in the presence of carboxymethyl chitosan. The nanosheets were composed of amorphous nitrogen doped carbon and molybdenum disulfide (MoS2 -NC). Notably, the one-dimensional tubular framework possessed low impedance characteristics. Through the way of combining it with nanosheets which had abundant defects, it could boost the charge transfer and improve the sodium storage performance effectively. When tested as the anode material of SIBs, this ZnS@MoS2 -NC composite exhibited excellent cycling and rate performance. Moreover, it was further assembled into sodium-ion full batteries and showed good cyclic stability. This work provides a valuable option for preparing promising SIBs anode materials by combining structural design with multi-component coordination, which can be extended to other metal sulfide electrode materials.